Transcranial Doppler in 150 Congolese children with sickle cell disease - Kazadi, Gisele Tshiama; Mbuyi, Didier Mukendi; Kitenge, Robert; Mpaka, Smith; Gini, Jean Lambert Ehungu; Ngiyulu, René; Tshilolo, Léon Muepu (Frontiers in Stroke, 2024)
Introduction Sickle Cell Disease (SCD) ranks among the most prevalent genetic disorders globally. The incidence in sub-Saharan African countries has been estimated to be 230.000/y with a high prevalence (1%) in the Democratic Republic of Congo (DRC). Stroke is a significant complication of Sickle Cell Disease (SCD), and carries a high risk of disability and mortality. Transcranial Doppler (TCD) is currently the non-invasive exploration recommended for the prevention of stroke in young SCD patients. Objective To determine the prevalence of pathological TCD in a population of young Congolese SCA patients and to assess its association with hematological parameters. Population and methods This cross sectional study was carried out on 150 Congolese SS homozygous children between the ages 2–16 years old (mean age: 8.5 ± 4.0 years) in stable condition, and followed from January 1 to December 31, 2013. TCD was performed using the STOP I method in the main cerebral arteries. The risk of stroke was absent when the average maximum speed during a cycle (TAMMV) in middle cerebral artery (MCA) was < 170 cm/s, but present when TAMMV was borderline or conditional for values between 170 and 199 cm/s and pathological for values ≥ 200 cm/s. Results The prevalence of pathological TCD was 4% while the conditional TCD prevalence was 10%. The Mean blood velocity in MCA was 114.0 cm/s. There was a significant difference in the means of WBC (p = 0.003), Hb (p < 0.001), Hct (p < 0.001), MCV (p = 0.005) parameters when comparing normal and at risk TCD (conditional and abnormal). However, no significant association was found for the categorical corresponding parameters Conclusion Globally, 14% of patients were at risk of stroke, hence the interest in integrating TCD in the routine monitoring of children with SCD in order to prevent overt stroke by implementing a chronic blood transfusion program or the use of hydroxycarbamide.